2005
DOI: 10.1086/428837
|View full text |Cite
|
Sign up to set email alerts
|

Avascular Necrosis in HIV‐Infected Patients: A Case‐Control Study from the Aquitaine Cohort, 1997–2002, France

Abstract: Using a case-control study design, we studied the factors associated with HIV-related avascular necrosis (AN). During a 6-year period, 12 symptomatic AN cases were validated, and each case was individually matched with 3 control cases. A conditional logistic regression model showed that current alcohol consumption and a history of steroid use were the only factors associated with the occurrence of AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 27 publications
5
23
1
1
Order By: Relevance
“…4,6,9,11 Our data for steroid exposure are broadly comparable to that of Fessel et al, 13 in terms of aggregate corticosteroid dose given per month prior to AVN diagnosis and the dose given in the year prior to AVN diagnosis. In addition, the proportion who had received corticosteroids in the year prior to AVN diagnosis was 5/15 (33%) in our data compared with (3/12) 25% for Fessel et al Suggestions of how steroid exposure mediates cell death include increased apoptosis through activation of free radicals and inflammatory mediators, 4 increased intraosseous pressure due to fat infiltration of bone marrow causing obstruction in small blood vessels 11 or fat embolization in vessels through secondary hyperlipidaemia.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…4,6,9,11 Our data for steroid exposure are broadly comparable to that of Fessel et al, 13 in terms of aggregate corticosteroid dose given per month prior to AVN diagnosis and the dose given in the year prior to AVN diagnosis. In addition, the proportion who had received corticosteroids in the year prior to AVN diagnosis was 5/15 (33%) in our data compared with (3/12) 25% for Fessel et al Suggestions of how steroid exposure mediates cell death include increased apoptosis through activation of free radicals and inflammatory mediators, 4 increased intraosseous pressure due to fat infiltration of bone marrow causing obstruction in small blood vessels 11 or fat embolization in vessels through secondary hyperlipidaemia.…”
Section: Discussionsupporting
confidence: 79%
“…Established risk factors for AVN in individuals without HIV (such as alcohol abuse, corticosteroid use, coagulopathies) may be more prevalent in those with HIV. [4][5][6][7][8][9][10][11] Moreover, it has been suggested that HIV infection itself and antiretroviral therapy (ART), particularly protease inhibitors (PIs), 12 may increase AVN risk. This study investigates the association of AVN in HIV-positive individuals with possible risk factors including ART.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was supported by a univariable association of AVN with a CD4 nadir >200 cells/µL and corticosteroid use >3 months. Prolonged corticosteroid treatment is more often used in late presenters (eg, as adjunctive treatment to opportunistic infections) or subsequent to ART start (eg, management of immune reconstitution inflammatory syndrome) [5, 6, 10, 12, 20, 21]. In contrast to other studies, we did not observe an association with the use of testosterone or megestrol acetate.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to other studies, we did not observe an association with the use of testosterone or megestrol acetate. Alcohol use has previously been reported as a risk factor for AVN among HIV-positive persons [6, 10, 20, 21]. The longitudinal design of the SHCS including our quantitative assessment of alcohol consumption at 6-monthly intervals in the SHCS since 2008 [13] allowed us to extend these findings.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation